Young people and digital culture: critical approaches from Latin America - Ricaurte Quijano, Paola (2018)
Studies on youth and digital culture in academic literature tend to characterize the profile of young, connected, and urban communities that participate in digital environments as places of interaction, identity building, learning, leisure, political participation. In Latin America, it is essential to understand the meaning of youth digital practices from a situated and diachronic perspective, as well as to promote studies that explain how the sociotechnical dimension is anchored to dominant frameworks that outline its appropriation and the production of subjectivities. This text seeks to contribute to the reflection on digital youth cultures in the Latin American context. It presents less visible experiences of digital practices that explore epistemic disobedience and resistance through technological occupation.